2023
DOI: 10.1101/2023.08.29.23293788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pilot Clinical Validation of a Machine Learning Platform for Noninvasive Smartphone-Based Assessment of Corneal Epithelial Integrity

Andrew Y. Zhang,
Jayanth S. Pratap,
James R. Young
et al.

Abstract: Purpose: Fluorescein staining (FS) is a standard method of assessing corneal epithelium (CE) integrity. However, the equipment and personnel required for FS may be unavailable in low-resource environments. We developed and validated a low-cost, noninvasive, and quantitative CE evaluation pipeline using a custom smartphone attachment and convolutional neural networks (CNNs). Methods: A 3D-printed smartphone attachment and placido disk illumination module was attached to a OnePlus 7 Pro smartphone. 26 smartphone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…to validate a corneal epithelium (CE) evaluation pipeline using a custom smartphone attachment and CNNs. 33 The results showed that the smartphone-based CE evaluation tool in calculating areas of CE disruption had qualitative concordance with those revealed by fluorescein staining slit-lamp photos graded by two clinicians. Apart from AI models, it should be noted that specialized equipment like slit-lamp is still necessary for smartphone-based anterior segment imaging and the smartphone camera is in need of a short focus distance to scan the ocular surface and high resolutions to capture the images.…”
Section: Resultsmentioning
confidence: 66%
“…to validate a corneal epithelium (CE) evaluation pipeline using a custom smartphone attachment and CNNs. 33 The results showed that the smartphone-based CE evaluation tool in calculating areas of CE disruption had qualitative concordance with those revealed by fluorescein staining slit-lamp photos graded by two clinicians. Apart from AI models, it should be noted that specialized equipment like slit-lamp is still necessary for smartphone-based anterior segment imaging and the smartphone camera is in need of a short focus distance to scan the ocular surface and high resolutions to capture the images.…”
Section: Resultsmentioning
confidence: 66%